The positive correlation between DJ‐1 and β‐catenin expression shows prognostic value for patients with glioma. Issue 6 (28th May 2013) - Wang, Chao; Fang, Mao; Zhang, Meng; Li, Weiping; Guan, Hong; Sun, Yanhua; Xie, Siming; Zhong, Xueyun
<x xml:space="preserve">Abstract</x> The relationship between DJ‐1 and β‐catenin, and its impact on the prognosis for glioma patients has not been fully understood. This study determined the effect of DJ‐1 on β‐catenin and the prognostic significance of this interaction in glioma patients. We collected tumor specimens from 88 glioma patients and determined the expression of DJ‐1, β‐catenin and PTEN by using immunohistochemical staining. The involvement of DJ‐1 and β‐catenin in glioma cell lines was evaluated by immunohistochemistry and Western blotting. High DJ‐1 expression (37.5%) and high β‐catenin expression (34.1%) in glioma specimens were significantly associated with high grade and poor prognosis in glioma patients. However, only high levels of DJ‐1 (P = 0.014) was a strong independent prognostic factor, correlated with a reduced overall survival time. In vitro DJ‐1 expression was positively correlated with the expression levels of β‐catenin and p‐Akt, and negatively correlated with PTEN expression in U87, U251 MG, SWO‐38 and SHG44 human glioma cell lines. After the knockdown of DJ‐1, Akt, p‐Akt or β‐catenin expression levels were not affected in the PTEN‐null cell lines (U87 and U251 MG). However, in the SWO‐38 cell line, which has wild‐type PTEN protein, the level of PTEN increased while Akt/p‐Akt and β‐catenin levels were reduced. Furthermore, β‐catenin staining weakened in SWO‐38 cells after DJ‐1 levels decreased according to immunocytochemical analysis. In conclusion, DJ‐1 and β‐catenin may contribute to the development and recurrence of glioma and are valuable prognostic factors for glioma patients. DJ‐1 may regulate β‐catenin expression via PTEN and p‐Akt.